Observational study investigating the relationship between maxillomandibular characteristics and temporomandibular disc conditions in female patients with a skeletal class III pattern - Supakorn Suntornchatchaweach; Kenji Hoshi; Kazutoshi Okamura; Kazunori Yoshiura; Kamonwan Soonklang; Ichiro Takahashi (Journal of Orthodontic Science, 2023)
OBJECTIVES: The objective of this study was to analyze the relationship between maxillomandibular characteristics and the severity of temporomandibular disc displacement in female patients with a skeletal class III (SKIII) pattern. METHODS: Fifty-seven samples were included in the study. The evaluation of articular disc conditions was conducted using magnetic resonance imaging, while 25 cephalometric variables from lateral and postero-anterior (P-A) cephalograms were measured to determine their maxillomandibular characteristics. The samples were categorized into three groups based on the articular disc conditions: (1) normal disc position (NDP), (2) disc displacement with reduction (DDwR), and (3) disc displacement without reduction (DDwoR). The relationship between the maxillomandibular characteristics and disc conditions was examined through both basic statistical analysis and multivariate analysis using principal component analysis (PCA). RESULTS: The Kruskal–Wallis and Dunn–Bonferroni tests revealed a significant difference between the groups in terms of the deviation of mandibular characteristics observed on the P-A cephalogram. The DDwoR group exhibited significantly larger menton deviation, ramal height asymmetry index, and total mandibular length asymmetry index compared to the NDP and DDwR groups. Moreover, the PCA successfully extracted all cephalometric variables into eight principal components. Among them, only the principal component related to mandibular asymmetry was able to differentiate the SKIII samples with DDwoR from the other groups. CONCLUSIONS: The findings of this study highlight a significant relationship between mandibular asymmetry and the severity of disc displacement, particularly DDwoR, in female patients with a SKIII pattern.